Digital Expansion and Global Islamic Da'wah: The Relevance of Digital Khutbah in Historical Perspective - Rokibullah, Rokibullah (Sekolah Tinggi Agama Islam Kuningan, 2025)
The development of digital technology has brought fundamental changes in the practice of Islamic da'wah, especially through the shift in the medium of khutbah from physical space to digital platforms. Digital sermons are now not only a means of delivering religious messages, but also an instrument of establishing the authority, identity and solidarity of Muslims on a global scale. This research aims to: (1) trace the evolution of khutbah from the classical period to the digital era, (2) analyze the role of digital khutbah in expanding the reach of global Islamic da'wah, and (3) assess the relevance of digital khutbah in maintaining religious authority in the midst of the information age. This research uses a qualitative approach with historical-critical methods and thematic analysis, based on a study of 50 digital sermons from international da'wah figures disseminated through platforms such as YouTube and podcasts. The results show that digital khutbahs retain their classic moral and educative functions, but evolve in the context of visualization, interactivity and global audience response. Dominant themes include tawhid, ummah solidarity and digital ethics. In addition, this study found that digital khutbahs contribute to the democratization of religious authority, where credibility is determined more by digital connectivity and participation than traditional authority structures. Thus, digital khutbah is an adaptive and relevant medium of da'wah in responding to the challenges of Muslims in the era of information globalization.